Early pulmonary rehabilitation recommended decision-making behavior experience among pediatric intensive care unit medical staff: a qualitative study - Cai, WenQian; Li, Meng; Li, ChengCheng; Li, Mei; Zhao, XiaoKe; Zuo, YaHui; Zhang, Lu; Yang, YuYing (Frontiers in Pediatrics, 2025)
BackgroundTo understand the reasons for hindering and promoting the recommended decision-making behaviors for early pulmonary rehabilitation of PICU medical staff, and to provide a basis for developing corresponding management plans.MethodsBased on the Capability, Opportunity, Motivation-Behavior (COM-B) model and Theoretical Domains Framework (TDF), interview outlines were developed. A descriptive qualitative research method was used, and a purposive sampling method was employed to select medical staff from the intensive care unit of a tertiary children's hospital in Nanjing from September to December 2023 for semi-structured interviews. The interview data were coded using the COM-B and TDF frameworks, and analyzed, summarized, and refined using the Colaizzi 7-step method to extract themes.ResultsFour main themes and 13 sub-themes were extracted, including the need for pulmonary rehabilitation knowledge and skills, the experience of implementing pulmonary rehabilitation in critically ill children, communication and collaboration in the PICU rehabilitation platform, and external support for PICU pulmonary rehabilitation.ConclusionIn the process of recommending early pulmonary rehabilitation for critically ill children, departments should help PICU medical staff change their views on pulmonary rehabilitation and acquire relevant knowledge and skills, strengthen multidisciplinary cooperation, optimize external support, and create a good practice environment for the implementation and promotion of early pulmonary rehabilitation for critically ill children.